Death rates for asthma in English populations 1979-2007: comparison of underlying cause and all certified causes. - Goldacre, M; Duncan, M; Griffith, M (2012)
OBJECTIVE: To report on trends in mortality for asthma using all certified causes of death mentioned on death certificates (conventionally termed 'mentions'), not just the underlying cause. STUDY DESIGN: Retrospective analysis using death certificate information and population data. METHOD: Analysis of mortality records in the Oxford region (mentions available from 1979 to 2007) and English national data (mentions available from 1995 to 2007). The data were considered in periods defined by different national rules for selecting underlying cause of death (1979-1983, 1984-1992, 1993-2000, 2001-2007), and were also analysed as single calendar years. RESULTS: In Oxford, underlying cause mortality rates per million population in the four periods were 25, 32, 22 and 15, respectively. Rates for mentions were 44, 47, 41 and 29, respectively. Rule changes exaggerated the increase in underlying cause mortality in 1984-1992 (when 67% of asthma deaths were coded as underlying cause). Conversely, the decrease in underlying cause mortality for asthma by 2001-2007 is less than it seems (because just under 50% of asthma deaths in 2001-2007 were coded as underlying cause). Comparisons of trends in asthma and chronic obstructive airways disease (COPD) for individuals aged ≥ 55 years showed a decrease for both asthma and COPD in men; in women, a decrease in asthma and an increase in COPD was seen from the early 1990s. CONCLUSIONS: Approximately half of all deaths certified for asthma are missed when asthma mortality is analysed using underlying cause alone. The long-term decreasing trend in asthma mortality is real, and is not attributable to a trend in transferring certification from underlying to contributing cause. Nonetheless, caution is needed when comparing asthma deaths using underlying cause alone across periods that include changes to rules for the selection of underlying cause.